The Design and Implementation of 2k/4k/8k Pipeline FFT-IFFT Core for DVB-T and DVB-H - FOURMAN DUTA AKBAR SUDIRDJA (NIM 13204227), ANDY'ES
DVB-H and DVB-T digital television standards are issued by the DVB consortium in Europe. DVB-T is used for a static digital television transmission (terrestrial) and DVB-T is used for a mobile digital television transmission. Both DVB standards use OFDM modulation techniques. This allows modulation between its adjacent sub-carriers without interference. Modulation technique uses a modifier module IFFT signal data from frequency domain to time domain. While at the demodulation part, FFT module is used to change the return signal from the output of the IFFT and converted them from the time domain into the frequency domain.